Cardiovascular CT for evaluation of single-ventricle heart disease: risks and accuracy compared with interventional findings. (11th September 2017) - Han, B. Kelly; Huntley, Marnie; Overman, David; Witt, Dawn; Dassenko, David; Garberich, Ross F.; Lesser, John R.
Abstract: Objective: We sought to evaluate the risk and image quality from cardiovascular CT in patients across all stages of single-ventricle palliation, and to define accuracy by comparing findings with intervention and surgery. Methods: Consecutive CT scans performed in patients with single-ventricle heart disease were retrospectively reviewed at a single institution. Diagnosis, sedation needs, estimated radiation dose, and adverse events were recorded. Anatomical findings, image quality (1–4, 1=optimal), and discrepancy compared with interventional findings were determined. Results are described as medians with their 25th and 75th percentiles. Results: From January, 2010 to August, 2015, 132 CT scans were performed in single-ventricle patients of whom 20 were neonates, 52 were post-Norwood, 15 were post-Glenn, and 45 were post-Fontan. No sedation was used in 76 patients, 47 were under minimal or moderate sedation, and nine were under general anaesthesia. The median image quality score was 1.2. The procedural dose–length product was 24 mGy-cm, and unadjusted and adjusted radiation doses were 0.34 (0.2, 1.8) and 0.82 (0.55, 1.88) mSv, respectively. There was one adverse event. No major and two minor discrepancies were noted at the time of 79 surgical and 10 catheter-based interventions. Conclusions: Cardiovascular CT can be performed with a low radiation exposure in patients with single-ventricle heart disease. Its accuracy compared with that of interventional findings is excellent. CT is an effective advanced imaging modality when a non-invasive pathway is desired, particularly if cardiac MRI poses a high risk or is contraindicated.